2022
DOI: 10.1177/14791641221113788
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diabetes on long-term all-cause re-hospitalization after revascularization with percutaneous coronary intervention

Abstract: Purpose: The purpose of the study was to investigate the incidence, cause and probability of re-hospitalization within 30 and 365 days after percutaneous coronary intervention (PCI) in patients with diabetes. Method: Between January 2010 and September 2014, 2763 patients with diabetes were treated with PCI at two Hospitals in Western Denmark. Reasons for readmission within 30 and 365 days were identified. Results: Readmission risks for patients with diabetes were 58% within 365 days and 18% within 30 days. Rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Moreover, increased risks of death, MI, and revascularization have been observed in diabetic patients undergoing PCI 40 . In a study by Hansen et al, the authors showed that more than half of the diabetic patients undergoing PCI had readmissions within one year, which was increased by the presence of other risk factors 41 . This finding was observed in other studies as well 42 , 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, increased risks of death, MI, and revascularization have been observed in diabetic patients undergoing PCI 40 . In a study by Hansen et al, the authors showed that more than half of the diabetic patients undergoing PCI had readmissions within one year, which was increased by the presence of other risk factors 41 . This finding was observed in other studies as well 42 , 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our results, researchers have explored the relationship between FBG levels and readmission rates in patients with HF. One retrospective study analyzed the association between glycemic status, including FBG, and readmission rates in HF patients with diabetes mellitus [12]. They found that higher FBG levels were associated with a higher risk of all-cause readmission and cardiovascular readmission.…”
Section: Discussionmentioning
confidence: 99%